STRATEGI PROGRAM KOMUNIKASI KORPORASI Studi Kasus Pada PT Djarum Pasca PP 81/1999 dan Revisinya PP38/2000 - Salihul Hadi (Jurnal Studi Komunikasi dan Media, 2011)
The research was motivated by the emergence of the phenomenon of disruption on Corporate Communications Program Strategy / Corporate Communication PT. Djarum in the conduct of Communications towards Stakeholders, in relation with the enactment of PP 81/1999 and its revision namely PP38/2000. Research questions include : How do strategy program on Corporate Communications  PT Djarum in communicate with Stakeholders after PP81/1999 and its revisión PP38/2000 enacted ? Using the case study method, the result showed: activity of Corporate Communications   handled by the  Public Relations of PT Djarum. Using the case study method, results showed: activity of Corporate Communications   handled by the  Public Relations of PT Djarum. Public Relations is the task of maintain and develop trust in stakeholders relationship. Stakeholders are the groups that are within (internal) or outside the company (external) that have a role in determining the success of the company. Internal stakeholders are its shareholders, managers / top executives, employees and their families. External stakeholders are customers, suppliers, distributors, competitors, banks, government, press, and NGOs. Activity of Corporate Communications through the Public Relations that gave rise to the SWOT analysis, composing  the objective and target ,  and setting clear targets, carried out in accordance with the concept of Public Relations.Penelitian ini dilatarbelakangi oleh kemunculan fenomena terganggunya Strategi Program Komunikasi Korporasi/Corporate Communication PT. Djarum dalam melakukan kegiatan Komunikasi Terhadap Stakeholders, sehubungan dengan keluarnya PP 81/1999 dan Revisinya PP38/2000. Pertanyaan penelitian berupa : Bagaimana strategi program Komunikasi Korporasi PT. Djarum dalam melakukan kegiatan Komunikasi antara PT Djarum dengan Stakeholdersnya Pasca PP81/1999 dan Revisinya PP38/2000? Dengan menggunakan metode penelitian studi kasus hasilnya menunjukkan :  Aktifitas Corporate Communications ditangani oleh pihak Public Relations PT Djarum. Tugas Public Relations.yaitu merawat dan mengembangkan kepercayaan Stakeholders. Stakeholder adalah kelompok-kelompok yang berada di dalam (internal) maupun di luar perusahaan (eksternal) yang mempunyai peranan dalam menentukan keberhasilan perusahaan. Stakeholder internal diantaranya pemegang saham, manajer/top eksekutif,   karyawan   beserta   keluarganya.   Sedangkan  stakeholders   eksternal  diantaranya konsumen, pemasok, penyalur, pesaing, bank, pemerintah, pers, dan lembaga swadaya masyarakat. Aktifitas corporate communications melalui Public Relations yang memunculkan analisis SWOT, penyusunan objektif, dan penetapan target sasaran yang jelas,  dilakukan sesuai dengan konsep Public Relations.